Perancangan Buku Pedoman Konsumen Cerdas Dengan Teknik Komik Strip Sebagai Upaya Meningkatkan Kesadaran Remaja di Kota Surabaya - Permatasari, Shinta Dwi; Budiardjo, Hardman; Yosep, Sigit Prayitno (Jurnal Art Nouveau, 2017)
The habit of teenagers to follow the new trend, make them more interested to buy somethings outside their needs buy by desire. This attitude fosters a consumption culture in the adolesecents, which not careful before buy somethings. Therefore, many sellers use it to commit fraud. In order not always to be victim, teenagers need to be closer with media which can invite them to be aware to become smarth consumer trough a smart consumer handbook.Kata Kunci: Buku Pedoman, Konsumen Cerdas, Komik Strip, Intellegent